The Complex and Well-Developed Morphological and Histological Structures of the Gastrointestinal Tract of the Plateau Zokor Improve Its Digestive Adaptability to High-Fiber Foods - Xincheng Cai; Darhan Bao; Guohui Ye; Bin Chu; Zhuangsheng Tang; Rui Hua; Limin Hua (Animals, 2022)
The morphological and histological traits of the gastrointestinal tract (GIT) enable the animal to perform some specific functions that enhance the species’ adaptability to environments. The plateau zokor (Eospalax baileyi) is a subterranean rodent that mainly forages on plant roots in the Qinghai-Tibet Plateau, but little is known about the mechanism by which the plateau zokor digests roots that have high fiber contents. In this study, we used comparative anatomy methods to compare the morphological and histological traits of the GIT of both the plateau zokor and the plateau pika (Ochotona curzoniae), a small, fossorial lagomorph that forages aboveground plant parts, in order to clarify the traits of the plateau zokor’s GIT and to understand its adaptations to high-fiber foods. The results showed that the foods which plateau zokors eat have a higher fiber content than those which the plateau pikas eat. The plateau zokor has a double-chambered and hemi-glandular stomach (the tubular glands are only in the gastric corpus II, and the gastric fundus is keratinized), whereas the plateau pika has a simple, wholly glandular stomach. The gross morphological indicators (organ index and relative length) of the GIT were significantly lower in the plateau zokor than they were in the plateau pika (p < 0.001). However, the thickness of the gastric corpus II mucosal layer and the gastric fundus muscle layer are significantly higher in the plateau zokor than they are in the plateau pika (p < 0.001), and the thickness of each layer of intestinal tissue is higher in the plateau zokor than it is in the plateau pika. Additionally, the small intestinal villi also are higher and wider in the plateau zokor than they are in the plateau pika. Our results suggest that instead of adapting to digest the high-fiber diet by expanding the size of the GIT, the plateau zokor has evolved a complex stomach and a well-developed gastrointestinal histological structure, and that these specialized GIT structures are consistent with an optimal energy-economy evolutionary adaptation strategy.